Alumina and Hafnia ALD Layers for a Niobium-Doped Titanium Oxide Photoanode - Naji Al Dahoudi; Qifeng Zhang; Guozhong Cao (International Journal of Photoenergy)
Niobium-doped titanium dioxide (TiO2) nanoparticles were used as a photoanode in dye-sensitized solar cells (DSCs). They showed a high photocurrent density due to their higher conductivity; however, a low open-circuit voltage was exhibited due to the back-reaction of photogenerated electrons. Atomic layer deposition is a useful technique to form a conformal ultrathin layer of Al2O3 and HfO, which act as an energy barrier to suppress the back electrons from reaching the redox medium. This resulted in an increase of the open-circuit voltage and therefore led to higher performance. HfO showed an improvement of the light-to-current conversion efficiency by 74%, higher than the 21% enhancement obtained by utilizing Al2O3 layers.